TYPOLOGY OF CHRONOTOPE MODELLING IN THE NOVELLA «POVOROT» BY YURII YANOVSKYI AND «AN OCCURRENCE AT OWL CREEK BRIDGE» BY AMBROSE BIERCE - Мафтин, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article conducts research into specifics of the chronotope modelling in the novellas “Povorot” by Yu. Yanovskyi and “An Occurrence at Owl Creek Bridge” by A. Bierce. The typological analysis of peculiarities of constructing temporal-spatial coordinates in the creations by the Ukrainian and the American writers permitted to expose their mastery in the realm of the novella composition. Both authors of the novellas artfully employed the spatial-temporal composition as a special, conscious fictional method. In both authors’ novellas the analogous methods of depiction of social-historical time are used, characteristic double denouement enhances an emotional effect. Thanks to the use of the technique of concentric transitions of a sleep into a sleep and “pseudo-wakenings” in Yu. Yanovskyi as well as to the character’s visions in a cataleptic condition in A. Bierce in real fact plots without fabula unfold into structures full of events.